Analisis Yuridis Penerapan Tindak Pidana Ketidakhadiran Tanpa Izin Paling Lama Empat Hari Di Dalam Kitab Undang-Undang Hukum Pidana Militer - Renaldi, Reno; Nawi, Syahruddin; Arsyad, Nasrullah (Universitas Pahlawan Tuanku Tambusai, 2024)
Examining the Application of the Offense of Unauthorized Absence for a Maximum of Four Days in the Military Penal Code: A Juridical Analysis.The Indonesian National Armed Forces (TNI) not only serve as the primary force of the national defense system of the Republic of Indonesia but also fulfill the responsibility of implementing state defense policies to uphold national sovereignty, preserve territorial integrity, protect the nation's safety, carry out military operations for war and military operations other than war, and actively participate in regional and international peacekeeping missions as a component of national security support, thereby ensuring the effective realization of the principles of Pancasila in line with the unity of the Indonesian Unitary State. The objective of this study is to examine the provisions or regulations in the military, specifically pertaining to the unauthorised absence of TNI personnel for a maximum of four days under the Military Penal Code subsequent to the implementation of the Indonesian Law Number 25 of 2014 concerning Military Discipline Law. The primary data were directly acquired from the research site, encompassing records of instances pertaining to Unauthorised Absence for a duration of up to four days throughout the years 2022-2023. Secondary data were acquired by a comprehensive examination of literature, whilst tertiary data covered a range of letters, reference books, and official papers released by pertinent authorities.The findings reveal the existence of TNI personnel who engage in unauthorized absence for a maximum of four days, which constitutes a criminal offense within the Military Penal Code and is considered an act of indiscipline according to the Indonesian Law Number 25 of 2014 concerning Military Discipline Law, thereby subject to disciplinary punishment. The research findings emphasise the alignment between the Military Penal Code and the Indonesian Law Number 25 of 2014, which pertains to Military Discipline Law. This alignment specifically addresses the issue of unauthorised absence for a maximum of four days, aiming to eliminate any ambiguity or differing viewpoints and ensure legal certainty.